Pengembangan Lembar Kerja Peserta Didik Berbasis Science, Technology, Engineering, and Mathematics untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik (UPEJ Unnes Physics Education Journal, 2019)
The goals of this research are to describe the characteristics of student worksheets based on STEM, to know the feasibility of student worksheets based on STEM, to know the readability of student worksheets based on STEM, and to know the improvement of students' ability in their creative thinking. The used method in this research is Research and Development (R&D). This research consists of four-step; they are preliminary study, product design, design validation, and product testing. One Group Pretest-posttest is used as the trial design. The subject of a small-scale trial is XI MIPA 1 and the subject of a large-scale trial is XI MIPA 2 SMA Negeri 1 Jekulo Kudus. The characteristics of STEM-based is that student worksheets contain discussion and practicum activities about mechanical waves associated with STEM aspects. The result of advisability test in terms the aspects of content, presentation, and language as much as 85.21% indicates that the STEM-based student worksheets to improve the ability of creative thinking is very feasible to use. Readability test results of 89.66% indicate that STEM-based student worksheets are easy to understand. Based on large-scale trials, the STEM-based student worksheets can improve the ability to think creatively, in terms of fluency, flexibility, elaboration, and originally indicated by the increase of pretest-posttest value.